Protection of citizens’ rights, public safety & police legitimacy: the legal equilibrium for public order - Keane, Jaclyn M. (Public Order Policing, 2024)
This chapter first discusses the constitutional foundation of free speech and assemblies as well as their possible limitations and challenges, especially for police, when executing such limitations. After a brief view of the relationship between the crowd and police, the authors discuss an example of the London Metropolitan Police (Met) to show some decisive decisions (and possible alternatives) which had a lasting negative effect on the relationship between the Met and their community. Finally, the authors shed some light on Law Enforcement legitimacy as well as the concept of “Policing with consent” and underpin with their conclusion the importance of balancing the legal equilibrium.